Issues and challenges of IFRS 9 in Malaysian Islamic financial institutions: recognition criteria perspective - Marziana Madah Marzuki; Abdul Rahim Abdul Rahman; Wan Amalina Wan Abdullah; Ainulashikin Marzuki; Nathasa Mazna Ramli (Emerald Insight, 2024)
Indexed by WOS/Scopus/ERA